Gestão de resíduos sólidos em áreas rurais : desafios e subsídios para o Programa Nacional de Saneamento Rural - Izabel Cristina de Matos Andrade (2023)
Sanitation services provided to the rural population in Brazil have high coverage deficits. Historically, investments in basic sanitation were concentrated in large urban centers, to the detriment of rural areas. The solutions adopted by rural communities for the management of solid waste generated on their properties result from local and individual decisions and, in general, aim to eliminate waste without worrying about environmental impacts. Launched in 2019, under the name “Rural Brazil Sanitation Program (PSBR)”, the “National Rural Sanitation Program(PNSR)” proposed a line of action for the management of solid waste represented by the collection of waste throughout the municipal territory and the installation of sorting and transshipment units, primarily at specific and strategic points, so that municipal waste (or even from a group of municipalities) is sent to sanitary landfills. Despite the advances that the reclassification of rural sectors by the PNSR allowed, in terms of delimitation of actions, this characterization proves to be limited with regard to the solutions practiced and the adequate service to the population. It is known that rural communities have peculiar characteristics that differentiate them from populations in urban areas. Therefore, the form of political action in the face of the challenges of bringing sanitation to rural areas becomes essential, prioritizing the use of effective instruments, aiming at understanding the existing diversity and the adoption of mechanisms of participation and social control necessary for the consolidation actions in rural areas and traditional communities. In this regard, the study in question aimed to analyze the management of solid waste in rural areas, proposing subsidies and identifying challenges for the implementation of the PNSR propositions. The methodology encompassed documentary research, content analysis of sanitation legislation and solid waste in force in Brazil and Minas Gerais, consensus opinion through the Delphi method with specialists in the sector and interviews using a semi-structured script with public managers from 23 municipalities representing the 12 mining mesoregions. The results showed that sanitation in rural areas is not included in the actions proposed by the laws that should provide guidelines for the universalization of services; the lack of technical and/or managerial structure in Brazilian municipalities, in the eyes of specialists, to carry out solid waste management as recommended by the PNRS and major deficits in the basic sanitation sector in the State of Minas Gerais, as well as the absence or insufficiency of reliable data in relation to rural areas, making it difficult to implement and improve actions in rural sanitation developed by the state and municipal governments. The adoption of governance networks is recommended in order to facilitate coordination through negotiated interaction between a plurality of political actors, subsidizing social participation and the implementation of the PNSR.